(untitled) (Acta Scientiarum. Biological Sciences, 2024)
Transcription factors are proteins encoded in an organism’s genome that regulate gene expression and control various biological activities. In fungi, many of these transcription factors are proteins with unidentified functions until now, particularly those that regulate genes associated with Candida albicans cell wall biosynthesis. This process is vital for fungal bioactivity and sensitivity to some antifungal agents. This study investigates Mig1 and Orf19.173 transcription factors in response to caspofungin in different environmental conditions as an initial step toward understanding their roles in cell wall biogenesis and drug resistance. A set of C. albicans mutant strains were exposed to caspofungin in Yeast Extract-Peptone-Dextrose (YPD) medium at 25°C and in RPMI 1640 medium (supplemented with 10% serum) at 37°C to simulate host conditions. Transmission electron microscopy (TEM) was used to analyze structural changes in the cell wall of Candida albicans isolates. The study found that mutant strains (mig1Î”/Î”) and (orf19.173Î”/Î”) were susceptible to Caspofungin in RPMI 1640 medium at 37°C but not on YPD medium at 25°C. Additionally, TEM images revealed that the cell wall of these mutant strains exhibited a noticeable thickness and numerous protrusions when exposed to caspofungin. Based on these findings, it was concluded that the transcription factors Mig1 and Orf19.173 promote cell wall biosynthesis in C. albicans when exposed to caspofungin in the host-like environment.